2016
DOI: 10.1016/j.hlc.2016.06.427
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Mitraclip Versus Mitral Valve Surgery for Severe Symptomatic Mitral Regurgitation

Abstract: sto the target SVG. Extent score, diabetes and patient's age at the time of the procedure were independently associated with risk of death on follow-up.Conclusions: Periprocedural troponin rise, diabetes and high SVG extent score are predictive of poorer long-term outcome following PCI. The effect of high extent score and diabetes persists past 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 0 publications
6
29
0
2
Order By: Relevance
“…Registry data also confirm that the majority of patients have a substantial clinical benefit with the relief of heart failure symptoms [25]. However meta-analysis data consisting of one randomised controlled trial and three prospective observational studies showed no mortality benefit at 12 months (7.4% vs. 7.3%; P = 0.66) in patients undergoing MitraClip implantation compared to surgical correction of severe MR [39]. It should be noted, however, that patients in the MitraClip group were significantly older, had significantly lower LVEF and significantly higher EuroSCORE.…”
Section: Discussionmentioning
confidence: 89%
“…Registry data also confirm that the majority of patients have a substantial clinical benefit with the relief of heart failure symptoms [25]. However meta-analysis data consisting of one randomised controlled trial and three prospective observational studies showed no mortality benefit at 12 months (7.4% vs. 7.3%; P = 0.66) in patients undergoing MitraClip implantation compared to surgical correction of severe MR [39]. It should be noted, however, that patients in the MitraClip group were significantly older, had significantly lower LVEF and significantly higher EuroSCORE.…”
Section: Discussionmentioning
confidence: 89%
“…The median length of stay, after a MitraClip procedure, is 2.4 days. 16 One of the tremendous advantages of this procedure is how well it is tolerated even in patients with severe LV dysfunction and elevated left atrial filling pressures. The short recovery times and length of hospitalization position this device favorably when compared to mitral valve repair or replacement in the high and extreme surgical risk group of patients.…”
Section: Overview Of Technologymentioning
confidence: 99%
“…Even in the pivotal EVEREST 2 clinical trial, major adverse events of death and major stroke were similar in both arms of the study. 3,16 Patients in the surgical arm had a higher need for blood transfusion and longer mechanical ventilation times than patients in the MitraClip arm. New onset atrial fibrillation and acute renal failure incidence were higher in the MitraClip group.…”
mentioning
confidence: 99%
“…Der Literatur folgend, dass die Behandlung einer funktionellen Mitralklappeninsuffizienz durch Mitralklappenringannuloplastie und Segelplastik eine hohe perioperative MortalitĂ€t ohne Überlebens-verbesserung aufweist, wird die operative chirurgische Behandlung sowohl in den europĂ€ischen als auch in den amerikanischen Leitlinien nur mit einem Klasse-IIb-Empfehlungsgrad versehen [3,4] In grĂ¶ĂŸerem Umfang wird bisher nur der MitraClipÂź eingesetzt, der in Beobachtungsstudien an einigen tausend Patienten eine primĂ€re Erfolgsquote zwischen 71 und 100% aufweist [10,11]. Auch in einer randomisierten Studie (EVEREST II) bei Patienten mit vorwiegend struktureller MI konnte das MitraClipÂź-Verfahren im Hinblick auf eine Reduktion der MI und eine klinische Verbesserung bestehen [12].…”
Section: Funktionelle Mitralinsuffizienzunclassified